Cytotoxic T Lymphocyte Antigen 4 Haploinsufficiency Presenting As Refractory Celiac-Like Disease: Case Report - Collen, Lauren V.; Salgado, Carlos Andres; Bao, Bin; Janssen, Erin; Weir, Dascha; Goldsmith, Jeffrey; Leichtner, Alan; Sabery Khavari, Nasim; Gernez, Yael; Snapper, Scott B. (Frontiers in Immunology, 2022)
Primary immunodeficiency may present with treatment-refractory enteropathy. We present two patients with celiac/celiac-like disease diagnosed in early childhood and refractory to the gluten-free diet. One patient had features of multi-system autoimmunity, while the other had celiac-like disease as an isolated clinical finding. Both patients underwent genetic testing given disease refractoriness and were ultimately diagnosed with CTLA4 haploinsufficiency. They are both now in complete clinical and endoscopic remission on abatacept. CTLA4 haploinsufficiency has incomplete penetrance and significant phenotypic heterogeneity but should be considered in the differential diagnosis of refractory celiac/celiac-like disease, as treatment implications are significant.